Associated factors to non-use of formal health services in the peruvian population: analysis of the national household survey (ENAHO) 2015 - Vicente A. Benites-Zapata; Michelle Lozada-Urbano; Diego Urrunaga-Pastor; Edith Márquez-Bobadilla; Enrique Moncada-Mapelli; Edward Mezones-Holguin (Revista Peruana de Medicina Experimental y Salud Pública, 2017)
The aim of the study was to estimate the prevalence of non-use of health services (NUHS) and its associated factors using the National Household Survey (ENAHO 2015). The participants were defined as NUHS if they have presented any symptoms, discomfort, illness, relapse of chronic illness or accident during the last month and did not go to the health services. 35036 participants were analyzed; the prevalence of NUHS was 53,9%. NUHS was higher in the coastal region (adjusted Prevalence Ratio [aPR]=1.24;95%CI:1.17-1.31), highlands (aPR=1.38;95%CI:1.31-1.46) and jungle (aPR=1.25,95%CI:1.18-1.33) compared to Lima. Likewise, there were a higher prevalence of NUHS in participants without health insurance (aPR=1.59;95%CI:1.52-1.66) and those affiliated to Ministry of Health insurance (aPR=1.16;95%CI:1.11-1.22) compared to those affiliated to Social Security. More than half of the participants suffered from NUHS, which was associated with geographical and health system conditions. It is required evidenced-informed public policies to improve this situation.